1998
DOI: 10.1029/98jb01076
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of subduction initiation at preexisting fault zones

Abstract: Abstract. We show that a new subduction zone can initiate at a preexisting dipping fault zone with reasonable plate forces, consistent with what is observed in the western Pacific. The dynamics of subduction initiation within a viscoelastic medium has been systematically explored with the finite element method. We investigate the compression of oceanic lithosphere with both force and velocity boundary conditions and track the thermal structure in which heat is transported by both advection and diffusion. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
239
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(254 citation statements)
references
References 36 publications
14
239
0
1
Order By: Relevance
“…The drawback of using a fault is the presence of a stress discontinuity at either end of the fault. The stress singularity in the mantle can be avoided by tapering the degree of coupling along the fault [Toth and Gurnis, 1998;van Hunen et al, 2000], but the discontinuity at the surface leads to inaccurate topography. In lowresolution models, using a discrete fault is preferable to a broad low-viscosity region, which is not capable of fully decoupling the two plates [Zhong et al, 1998].…”
Section: Plate Boundary Shear Zonementioning
confidence: 99%
“…The drawback of using a fault is the presence of a stress discontinuity at either end of the fault. The stress singularity in the mantle can be avoided by tapering the degree of coupling along the fault [Toth and Gurnis, 1998;van Hunen et al, 2000], but the discontinuity at the surface leads to inaccurate topography. In lowresolution models, using a discrete fault is preferable to a broad low-viscosity region, which is not capable of fully decoupling the two plates [Zhong et al, 1998].…”
Section: Plate Boundary Shear Zonementioning
confidence: 99%
“…Subduction initiation has been addressed primarily through numerical modeling (2)(3)(4)(5)(6)(7)(8)(9). These studies have demonstrated the need for a weak zone in the lithosphere to facilitate subduction.…”
mentioning
confidence: 99%
“…In "spontaneous" subduction initiation, a plate's increasing density with age may eventually cause it to sink into the underlying asthenosphere (10,14), whereas in forced subduction initiation, external plate forces are required to initiate subduction (3,5,15). Oceanic plates that are at least ∼10 My old are negatively buoyant (16) and may undergo either forced or spontaneous subduction initiation.…”
mentioning
confidence: 99%
“…[69] Several studies have shown that subduction zones may preferentially initiate along preexisting oceanic fracture zones [e.g., Casey and Dewey, 1984;Scholl et al, 1998;Lebrun et al, 1998;Toth and Gurnis, 1998]. We should thus expect fracture zones that parallel the main suture to be common in ancient zones of ocean-ocean or ocean-continent convergence.…”
Section: Discussionmentioning
confidence: 99%